Menguji Posibilitas Transplantasi Variasi Bantuan Keuangan Partai Politik di Indonesia (Studi Perbandingan di Kolombia, Brazil, Korea Selatan, dan Turki) - Garuda Era Ruhpinesthi; Muhammmad Hamzah Al Faruq (Jurnal Penelitian Hukum De Jure, 2023)
There are variations in political party Financial Assistances in various countries with various implications, both positive and negative. Besides, there are problems with political parties in Indonesia which in literatures are suspected to be related to the regulation of political party Financial Assistances. This research focuses on answering two research problems. First, what are the implications for the regulation of various models of Financial Assistances for political parties in Colombia, Brazil, South Korea, and Turkey referring to the aspects of free and fair elections, democratic politics, and corruption index? Second, how is the possibility of legal transplantation of political party Financial Assistances in order to solve the problems of political parties in Indonesia? This research is socio-legal research that analyzes secondary data. The results of this study show two results. First, it shows that the law in four countries have different implications, which there are three notes namely that i) countries that are quite good in the aspect of free and fair elections are South Korea, Brazil, and Colombia, ii) the four countries are not good enough in the aspect of democratic politics, iii) countries that are quite good in the aspect of corruption index is South Korea. Second, it shows that there is the possibility of legal transplantation which there are three notes: i) there is a constant and dynamic variable regulation of political party Financial Assistances in Indonesia, ii) the problem of political party Financial Assistances in Indonesia is in the democratic politics and corruption index which means need to transplant several aspects, iii) there is a possibility of transplanting variations in political party Financial Assistances as long as certain conditions are fulfilled.